Implementation of the right to court and conducting remote hearings in civil proceedings. - Fibinger-Jasińska, Justyna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
The COVID-19 pandemic has introduced colossal changes in the functioning of courts. As it were, certain inevitable changes were accelerated, and the courts were forced to undergo digitization and open to remote operation, which was a more common phenomenon in other industries. The pandemic meant that not only the courts had to use distance communication programs to a greater extent, it happened in almost every industry. The purpose of introducing remote hearings during the pandemic was to enable the functioning of the courts without exposing the public to infection.